Influence of Sae‐regulated and Agr‐regulated factors on the escape of Staphylococcus aureus from human macrophages. (18th March 2016) - Münzenmayer, Lisa; Geiger, Tobias; Daiber, Ellen; Schulte, Berit; Autenrieth, Stella E.; Fraunholz, Martin; Wolz, Christiane
Summary: Although Staphylococcus aureus is not a classical intracellular pathogen, it can survive within phagocytes and many other cell types. However, the pathogen is also able to escape from cells by mechanisms that are only partially understood. We analysed a series of isogenic S. aureus mutants of the USA300 derivative JE2 for their capacity to destroy human macrophages from within. Intracellular S. aureus JE2 caused severe cell damage in human macrophages and could efficiently escape from within the cells. To obtain this full escape phenotype including an intermittent residency in the cytoplasm, the combined action of the regulatory systems Sae and Agr is required. Mutants in Sae or mutants deficient in the Sae target genes lukAB and pvl remained in high numbers within the macrophages causing reduced cell damage. Mutants in the regulatory system Agr or in the Agr target gene psmα were largely similar to wild‐type bacteria concerning cell damage and escape efficiency. However, these strains were rarely detectable in the cytoplasm, emphasizing the role of phenol‐soluble modulins (PSMs) for phagosomal escape. Thus, Sae‐regulated toxins largely determine damage and escape from within macrophages, whereas PSMs are mainly responsible for the escape from the phagosome into the cytoplasm. Damage of macrophages induced by intracellular bacteria was linked neither to activation of apoptosis‐related caspase 3, 7 or 8 nor to NLRP3‐dependent inflammasome activation.